Dinamika Pengaruh Eksternal dalam Pengambilan Keputusan Kebijakan Pertahanan - Sarjito, Aris (Jurnal Ilmu Sosial dan Humaniora, 2024)
In contemporary geopolitics, the formulation of defense policies is subject to a complex interplay of external factors, ranging from the influence of powerful actors to economic interests and ideational factors. This research aims to deepen our understanding of the external factors shaping defense policy decisions and their implications for national security strategies. Drawing upon qualitative research methods using secondary data analysis, this study investigates three key dimensions: "The Interplay of Power: External Actors and National Defense Policy," "The Intersection of Money and Muscle: Economic Interests in Defense Policy," and "The Power of Ideas: How Ideational Factors Shape Defense Policy." The findings reveal the significant role of external actors, such as superpowers and international organizations, in shaping defense policy decisions through various mechanisms of influence. Moreover, economic interests, including arms trade and energy security considerations, emerge as critical determinants of defense policy priorities. Furthermore, conceptual factors, such as security narratives and public perceptions of threats, profoundly influence defense policy formulation. This research contributes to the existing literature by comprehensively analyzing the multifaceted nature of external factors shaping defense policy decisions. The novelty lies in the holistic approach that integrates insights from political science, economics, and security studies. Keywords: defense policy, economic interests, external factors, ideational factors